Evaluación de los aislados fúngicos para la biodegradación de atrazina a nivel de laboratorio en la ESPAM MFL - Moreira Alcívar, Gema María (2023)
The present research was carried out in the Molecular Microbiology laboratory of the Veterinary Medicine major at ESPAM "MFL", "El Limón" site, Bolívar canton, with the objective of evaluating fungal isolates for the biodegradation of atrazine. For this purpose, three phases were established: in the selection of fungal strains potentially useful for atrazine biodegradation, different fungal strains were selected to evaluate their biodegradation percentage, which were chosen at random. To estimate the percentage of biodegradation of atrazine, it was necessary to sow the 48 fungal isolates in a PDA culture medium and then place in each strain a certain percentage of this herbicide (1%, 2% and 3%) and then incubate it; 24, 48 and 72 hours after its application, data were taken to calculate the biodegradation of atrazine with the proposed equation. On the other hand, the characterization at molecular level of the fungal strains was carried out with two types of fungi EM-64 and EM-134, these were the ones that reached the highest percentage of biodegradation with a halo of 77,5 cm and 121,81% and 75 cm halo and 117,88% respectively. It could be evidenced that the fungi belong to the family of Trichoderma longibrachiatum and Trichoderma orientale, presenting 99.63% of identity the strain EM-64 and 99.87% the strain EM-134. Concluding that it is fundamental to continue with investigations about fungal consortiums that provide a solution to remediate contaminated environments.